2005
DOI: 10.1093/eurpub/cki074
|View full text |Cite
|
Sign up to set email alerts
|

The Belgrade childhood diabetes study: a multivariate analysis of risk determinants for diabetes

Abstract: Among non-genetic factors, those affecting the child during pregnancy are especially important because of their preventability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 23 publications
5
24
1
Order By: Relevance
“…The more general MEDLINE search identified a further eight articles [33][34][35][36][37][38][39][40], and review of reference lists revealed another two articles [41,42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The more general MEDLINE search identified a further eight articles [33][34][35][36][37][38][39][40], and review of reference lists revealed another two articles [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…This observed increase in diabetes risk after Caesarean section delivery could not be explained by the confounding influence of birthweight, gestational age, maternal age, birth order, maternal diabetes or breastfeeding. Table 1 b Breast-feeding was categorised as breast-feeding at discharge from hospital [18,32], any breast-feeding [15,25,27], breast-feeding for approximately 3 months or more [30,40,43] and breast-feeding for approximately 4 months or more [37][38][39] Ref. cat., reference category…”
Section: Discussionmentioning
confidence: 99%
“…Sipetic et al [12] and Marshall et al [13] reported that +ve family history of type 1 diabetes has-consistently been reported to raise type 1 diabetes risk among relatives. These results were in contrast with the study of Edna-et al [14] that described the abrupt onset of type 1 diabetes and the absence of family history.…”
Section: Discussionmentioning
confidence: 99%
“…A number of processed meats contain nitrites and nitrates which can be converted to nitrosamines by interaction with amino compounds either in the stomach or within the food product. Nitrosamines have been found to be toxic to pancreatic beta cells and to increase the risk of type 1 and type 2 diabetes in animal studies [57][58][59], and of type 1 diabetes in some [60,61], but not all [62], epidemiological studies. Other possible mechanisms may involve advanced glycation end-products [63], increased levels of inflammatory mediators [13,47,64] and γ-glutamyltransferase [65], and lower levels of adiponectin [66] with high meat intake.…”
Section: Discussionmentioning
confidence: 99%